Abolitionist Feminism as Prisons Close: Fighting the Racist and Misogynist Surveillance “Child Welfare” System - Michalsen, Venezia (The Prison Journal, 2019)
The global prison industrial complex was built on Black and brown women’s bodies. This economy will not voluntarily loosen its hold on the bodies that feed it. White carceral feminists traditionally encourage State punishment, while anti-carceral, intersectional feminism recognizes that it empowers an ineffective and racist system. In fact, it is built on the criminalization of women’s survival strategies, creating a “victimization to prison pipeline.” But prisons are not the root of the problem; rather, they are a manifestation of the over-policing of Black women’s bodies, poverty, and motherhood. Such State surveillance will continue unless we disrupt these powerful systems both inside and outside prisons.
Keywords: dept.soc; peer-reviewed